Dialogue in Progress - Wissenschaft. Kultur. Gesellschaft. Stimmen aus 20 Karlsruher Gesprächen - Robertson-von Trotha, Caroline Y. [Hrsg.]Ianniello, Marco (KIT Scientific Publishing, 2017)
20 years, several hundred protagonists from all around the world, from New York to Mumbai to Cairo: the history and ideas of the ‹Karlsruhe Dialogues› are presented in many different voices in this special publication. The event series combines locality and globality, theory and practice, science and art, culture and society. It creates a forum for a diverse range of personalities, for controversies and for syntheses.